2001
DOI: 10.1103/physrevb.64.245109
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of oxygen-related defects inPbWO4andCaMoO4

Abstract: Several types of defect structures in PbWO 4 and CaMoO 4 are studied within the framework of density functional theory. While PbWO 4 is currently of greater technological interest, we were able to carry out more extensive calculations for CaMoO 4 , including lattice relaxation, large simulation cells, and more complicated defects. The structural and chemical similarity of the two materials suggests that their defect properties may also be similar. The electronic structure of isolated oxygen vacancies, oxygen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 45 publications
6
30
1
Order By: Relevance
“…At this stage, it has to be noted that Abraham et al also presented density-functional theory calculations of irregular PWO, 63 but their results are difficult to compare with ours because they created oxygen vacancies in a supercell while we only displaced some atoms, keeping their total number constant. Figure 9 illustrates the PL spectra recorded at room temperature for the PWO thin films heat treated at 200, 300, 400, and 500°C.…”
Section: ͑Pb͒ and 2p ͑O͒ Contributions While The Upper Cb Is Dominamentioning
confidence: 75%
“…At this stage, it has to be noted that Abraham et al also presented density-functional theory calculations of irregular PWO, 63 but their results are difficult to compare with ours because they created oxygen vacancies in a supercell while we only displaced some atoms, keeping their total number constant. Figure 9 illustrates the PL spectra recorded at room temperature for the PWO thin films heat treated at 200, 300, 400, and 500°C.…”
Section: ͑Pb͒ and 2p ͑O͒ Contributions While The Upper Cb Is Dominamentioning
confidence: 75%
“…[7][8][9] Defect-related properties have been widely investigated in semiconductors, such as Si, [10] TiO 2 , [11] ZnO, [12] and PbWO 4 . [13] The first-principle calculation, electron-spin resonance (ESR) spectroscopy, and temperature-programmed reduction (TPR) analysis show that photoabsorption in the visible region of the reduced TiO 2 can be attributed to oxygen vacancies caused by the reduction. [13][14][15][16] However, these semiconductors usually have a simple defect structure, while the optical absorption of insulating metal oxides has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The first-principle calculation, electron-spin resonance (ESR) spectroscopy, and temperature-programmed reduction (TPR) analysis show that photoabsorption in the visible region of the reduced TiO 2 can be attributed to oxygen vacancies caused by the reduction. [13][14][15][16] However, these semiconductors usually have a simple defect structure, while the optical absorption of insulating metal oxides has seldom been reported. The highly ionic nature of some materials, especially MgO, BaO, and Al 2 O 3 , allows the formation of many stable defect sites, including edges, corners, and anion/cation vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that oxide crystals of this family have many congenial features in their electronic structures that are preconditioned by the presence of similar molecular oxyanions XO 2− 4 in anionic positions of their lattice. The full-potential linear-augmented-plane-wave (FLAPW) method has been applied to studies of the electronic structures of perfect ZnWO 4 [6], PbWO 4 , CaWO 4 , CaMoO 4 and PbMoO 4 [7], CdWO 4 and CdMoO 4 [8], as well as of AXO 4 with several point defects [9,10]. Also the electronic structures of PbWO 4 , CdWO 4 and ZnWO 4 with point defects and impurities have been studied in the quantum chemical cluster approach [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%